Liderazgo orientado a la gente en call centers - León, Federico R. (2017)
Purpose – Call centers generate stress and absenteeism in staff and the literature suggests that peopleoriented leadership is the right way of supervision for such a situation. This study compared its effects versus those of other types of leadership. Methodology – Absentee data of 379 representatives of customer services of a Peruvian call center were analyzed and the representatives answered a questionnaire about the Framework of Values in Competition and its four types of leadership. Day and night work shifts were compared. Results – It was observed that absenteeism declines with people-oriented leadership although only during the day shift and the addition of leadership oriented to change results and control devalues models. Limitations/implications – Future studies should cover the performance of the worker. The findings suggest a need to re-focus the theoretical focus on environmental contingencies that affect leadership effectiveness. Originality/value – Leadership theorists will ask themselves in what circumstances the multiple leadership is effective. Call center managers will appreciate the organizational value of people-oriented leadership at the first level of supervision.